Applications of artificial intelligence technology in dentistry - Mohammad Hossein Ronaghi; Atefeh Bagheri (Tehran University of Medical Sciences, 2023)
Background and Aims: Artificial intelligence (AI) technology is widely used in dentistry in addition to numerous other sectors that impact human life, including medicine. A dentist can use AI technology to analyze patient data, diagnostic processes, and management activities. This study was conducted in Iran to identify the dental applications of AI and prioritize them. Materials and Methods: In the winter of 2022, this applied research was carried out in two stages using a mixed method. In the qualitative phase, 570 articles from 2011 to 2022 were identified in the databases of PubMed, Web of Science, Scopus and Google Scholar among the studies in the field of dentistry and related to artificial intelligence technology based on keywords and then the applications of artificial intelligence in dentistry were extracted. In the quantitative phase, the identified applications prioritized by a group of experts comprised 13 University faculty members with related research areas using the best-worst method (BWM). Results: The factors identified in the first stage of research were classified into six categories: implant and surgery, executive management, disease diagnosis, analysis of images, clinical prediction, and orthodontics. According to the experts' opinion, it was determined that medical photo analysis had the highest coefficient of importance (0.252) followed by orthodontics (0.234), disease diagnosis (0.151), implantology and surgery (0.143), clinical forecasts (0.127), and executive management (0.093). Conclusion: Dentists can use the capabilities of artificial intelligence in examining patients' teeth and diagnostic tests in dentistry based on the analysis of patient information. Information technology policymakers with the support and reinforcement of knowledge-based companies active in the field of artificial intelligence and joint investment in the field of medicine can be the basis for progress and the development of this technology in the country and the field of treatment.